Quality care for persons experiencing dementia: The significance of relational ethics - Sellevold, Gerd S (Nursing ethics, 2013)
The degree of success in creating quality care for people suffering from dementia is limited despite extensive research. This article describes healthcare providers’ experience with the ethical challenges and possibilities in the relationship with patients suffering from dementia and its impact on quality care. The material is based on qualitative, in-depth individual narrative interviews with 12 professional healthcare providers from two different nursing homes. The transcribed interview texts were subjected to a phenomenological–hermeneutical interpretation. To provide quality care to patients with dementia, the healthcare providers emphasized the importance of sensing and understanding the patients’ emotional and bodily expressions through sentient attentiveness and recognition of the patient as a person. They also described reciprocity of expressions in the relationship where the patient recognized them both as persons and healthcare providers. The analyses of the findings are, inter alia, discussed in light of Løgstrup’s relational philosophy of ethics.